METODOLOGI PENELITIAN HADIS DALAM APERSPEKTIF PEMIKIRAN NAWIR YUSLEM - Muhammad Qomarullah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
Nawir Yuslem is a scientist who wrestles with various scientific dimensions, both in Islamic law and hadith. With an educational background from the western sciences, it was also influenced by orientalist thinkers. But, planting a strong scientific tradition and Islam in the Minang community, the scientific acculturation made his thoughts on Islamic studies interesting. It can be seen from the way he combines terms in Hadith and semiotic theory as new offerings in hadith research in his book entitled "Hadith Research Methodology."